The Effectiveness of Group Problem-Solving Skills Training on Academic Achievement Motivation and Academic Self-Concept of Sixth-Grade Male Students in Iranshahr - Ariyan, Jaber; Sanagouye Moharer, Gholamreza; Karbalai Harafteh, Fatemeh Soghra (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aimed to determine the effectiveness of group problem-solving skills training on academic achievement motivation and academic self-concept of sixth-grade male students in Iranshahr. Methods and Materials: The statistical population of this quasi-experimental study included all sixth-grade male students in Iranshahr during the 2023-2022 academic year. Forty children who met the inclusion criteria were selected as the sample using multistage cluster sampling and were randomly assigned equally to an experimental group and a control group. The experimental group participated in an educational program on problem-solving strategies across 8 sessions, while the control group remained on a waiting list without receiving any training during this period. The primary data of this study were collected using Hermans’ Academic Achievement Motivation Questionnaire (1977) and Yessen-Chi’s Academic Self-Concept Questionnaire (2004). Data analysis was conducted in two parts: descriptive (central tendency and dispersion indices, skewness, and kurtosis) and inferential (multivariate analysis of covariance - MANCOVA) using SPSS-23 software. Findings: The results showed that group problem-solving skills training is effective in improving academic achievement motivation and academic self-concept among sixth-grade male students in Iranshahr. Conclusion: The findings of this study, in line with other research, confirm the efficacy of cognitive problem-solving interventions in enhancing academic achievement motivation and academic self-concept among students. Finally, the necessity of incorporating problem-solving skills training as part of school curricula and its impact on student behaviors and academic performance was discussed.